Interoperability and Reliability of Multiplatform MPLS VPN: Comparison of Traffic Engineering with RSVP-TE Protocol and LDP Protocol - Ismail, Nanang; Zaki, Eki Ahmad; Arghifary, Muhamad (CommIT (Communication and Information Technology) Journal, 2017)
One of the alternatives to overcome network scalability problem and maintaining reliability is using MPLS VPN network. In reallity, the current network is already using a multiplatform of several different hardware vendors, i.e., Cisco and Juniper platforms. This paper discusses the comparison of the simulation results to see interoperability of multiplatform MPLS VPN andreliability through traffic engineering using RSVP-TE and LDP protocols. Both the RSVP and LDP protocols are tested on a stable network and in a recovery mode,as well as non-load conditions and with additional traffic load. The recovery mode is the condition after the failover due to termination of one of the links in the network. The no-load condition means that the network is not filled with additional traffic. There is only traffic from the measurement activity itself. While network conditions with an additional load are conditions where there is an additional UDP packet traffic load of 4.5 Mbps in addition to the measurement load itself. On a stable network and without additional traffic load, the average delay on LDP protocol is 59.41 ms, 2.06 ms jitter, 0.08% packetloss, and 8.99 Mbps throughput. Meanwhile, on RSVP protocol, the average delay is 52.40 ms, 2.39 ms jitter, 12.18% packet loss, and 7.80 Mbps throughput. When failover occurs and on recovery mode, LDP protocol is48% of packet loss per 100 sent packets while on RSVP packet loss percentage is 35.5% per 100 sent packets. Both protocols have interoperability on the third layer of multiplatform MPLS VPN, but on heavy loaded traffic condition, RSVP protocol has better reliability than the LDP protocol.